BRANDING SEKOLAH: PENDEKATAN MANAJEMEN PEMASARAN DI ERA KOMPETITIF - Najwa Auliyatul Faizah; Anindya Dwi Salsabila; Nurul Asyifa; Hesti Kusumaningrum (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study investigates the marketing management approach to school branding in the competitive education era. The main objective is to analyze effective school branding strategies to improve the competitativeness of educational institutions. The methodology used is a quantitative method (library research) that includes a comprehensive analysis of current literature on educational marketing management and school branding. The main findings show that the implementation of branding strategies can enhance the school’s image, attract more talented students, and improve the institution’s competitiveness. It also shows the importance of integrating educational values into marketing strategies to maintain the integrity of the institution. Other recommendations include developing a comprehensive branding model, improving employee competencies in marketing management and continuously evaluating the effectiveness of branding strategy. This research contributes to a deeper understanding of the important role of branding in navigating an increasingly comprehensive educational environment.